2018
DOI: 10.2147/cmar.s174240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CT slice thickness on volume and dose evaluation during thoracic cancer radiotherapy

Abstract: IntroductionAccurate delineation of targets and organs at risk (OAR) is required to ensure treatment efficacy and minimize risk of normal tissue toxicity with radiotherapy. Therefore, we evaluated the impacts of computed tomography (CT) slice thickness and reconstruction methods on the volume and dose evaluations of targets and OAR.Patients and methodsEleven CT datasets from patients with thoracic cancer were included. 3D images with a slice thickness of 2 mm (2–CT) were created automatically. Images of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In terms of image quality, they are required to evaluate many quantitative parameters such as spatial resolution, image noise, low contrast, alignment, and slice thickness [11][12][13]. The latter parameter is important in the quality of CT images, since it has a direct impact on the image noise and accuracy of the 3D reconstruction of an image [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of image quality, they are required to evaluate many quantitative parameters such as spatial resolution, image noise, low contrast, alignment, and slice thickness [11][12][13]. The latter parameter is important in the quality of CT images, since it has a direct impact on the image noise and accuracy of the 3D reconstruction of an image [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The super-resolution imaging aims at improving the resolution in the axial plane by creating more pixels, while our goal is to improve the resolution in the longitudinal direction by creating more slices (densely sliced CT reconstruction from sparsely sliced CT data). Although creating a whole slice is much more difficult than creating a new pixel, this kind of study would be worthwhile because longitudinal resolution plays an important role on disease diagnosis [ 15 , 16 ]. However, we found that there are rare researches related to deep-learning-based resolution enhancement in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Slice thickness is one of the important parameters, and it has to be optimized as needed. Slice thickness affects the cross‐plane resolution of the clinical image, which then impacts the accuracy of the size determination of the organ 11,12 . The slice thickness also directly impacts image noise.…”
Section: Introductionmentioning
confidence: 99%